MiR-133a acts as a tumor suppressor in colorectal cancer by targeting eIF4A1. Issue 5 (April 2017) - Li, Wenfeng; Chen, Anqi; Xiong, Lingling; Chen, Ting; Tao, Fengxing; Lu, Yiyi; He, Qin; Zhao, Liang; Ou, Rongying; Xu, Yunsheng
Emerging evidence indicates that microRNAs play critical roles in carcinogenesis and cancer progression. In this study, miR-133a was found to be significantly downregulated in colon tumor tissues. We aimed to determine its biological function, molecular mechanisms, and direct target genes in colorectal cancer. From these results, we found that miR-133a was significantly downregulated in primary tumor tissues and colon cancer cell lines. Ectopic expression of miR-133a in colon cancer cell lines significantly suppressed cell growth, as evidenced by cell viability and colony formation assays, as well as reduced xenograft tumor growth in nude mice. However, the effect of miR-133a was abolished by the overexpression of eIF4A1. Moreover, miR-133a inhibited cellular migration and invasiveness. A luciferase activity assay revealed oncogene eukaryotic translation initiation factor 4A1 as a direct target gene of miR-133a, whose expression was inversely correlated with that of miR-133a. Our results demonstrate that miR-133a plays a pivotal role in colorectal cancer by inhibiting cell proliferation, invasion, and migration by targeting oncogenic eukaryotic translation initiation factor 4A1, which acts as a tumor suppressor and may provide a new potential therapeutic target in colorectal cancer.